Emperor of the universe - Marciano, Johnny; Chenoweth, Emily (Marciano, Johnny. Klawde (Series), 2020)
Klawde is not your basic cat. He's an emperor from another planet, exiled to Earth. He's cruel. He's cunning. He's brilliant ... and he's also Raj Banerjee's best friend. Following a humiliating, defeated effort to conquer Earth, Klawde has had it with this this dismal planet. And anyway, what's the point in conquering such an insignificant corner of the galaxy, when there's an entire universe to rule? Luckily for Klawde, the position of Emperor of the Universe is now open for the taking. So with Barx and Raj by his side, and enemies around every corner, Klawde begins the campaign of his life. Can he win enough hearts and minds to become . . . Emperor of the Universe? Heavily illustrated, with a hilarious, biting voice that switches between Raj's and Klawde's perspectives, this is the story of an unlikely friendship that emerges between a boy and the evil cat who arrived on his doorstep.